PVA/CM-chitosan/honey hydrogels prepared by using the combined technique of irradiation followed by freeze-thawing. (August 2015) - Afshari, M.J.; Sheikh, N.; Afarideh, H.
Abstract: Hydrogels with three components, poly(vinyl alcohol) (PVA), carboxymethylate chitosan (CM-chitosan) and honey have been prepared by using radiation method and radiation followed by freeze-thawing cycles technique (combinational method). The solid concentration of the polymer solution is 15 wt% and the ratios of PVA/CM-chitosan/honey are 10/1.5/3.5, 10/2/3, 10/3/2, and 10/3.5/1.5. The applied irradiation doses are 25, 30 and 40 kGy. Various tests have been done to evaluate the hydrogel properties to produce materials to be used as wound dressing. The results show that combinational method improves the mechanical strength of hydrogels while it has no significant effect on the water evaporation rate of gels. The combinational method decreases the swelling of hydrogels significantly, albeit this parameter is still acceptable for wound dressing. Microbiological analyses show that the hydrogel prepared by both methods can protect the wound from Escherichia coli bacterial infection. The wound healing test shows the good performance of the gels in mice. Highlights: Hydrogels prepared by the combination of irradiation and freeze-thawing methods. Hydrogels with improved mechanical strength prepared by the combinational method. The prepared hydrogels had acceptable transparency and degree of swelling. The water evaporation rates of these hydrogels were pretty low. Presences of honey in the formulation of gels led to a higher tissue regeneration.